A few ideas for teaching environmental physics. (17th October 2016) - Forinash, Kyle
Abstract: Unlike a typical university physics course there is no standardised syllabus for environmental physics. The topics covered also range beyond what is normally part of the physics curriculum, requiring the instructor to become knowledgeable about fields outside of physics. Some of these issues are complex and, unlike the laws of physics, change rapidly over time. This paper, based on 15 years experience teaching undergraduate environmental physics courses, both for non-science students and for students with strong backgrounds in the sciences, attempts to present a reasonable range of concepts and educational resources which could be included in an environmental physics course or added to an existing physics course as motivation for learning traditional physics concepts. An additional goal is to warn the reader of pitfalls they may encounter in trying to include material with which they may not be familiar. The approach is different from environmental courses taught in the social sciences in that the focus of an environmental physics course is on physical constraints to environmental solutions rather than limitations imposed by culture or politics.